استعادة المنظومات الغابية الرعوية لزيادة المرونة والإنتاجية بتونس - Jamel, Kailene; Louhaichi, Mounir (Food and Agriculture Organization of the United Nations, 2022)
The UNEP Regional Office for West Asia and the FAO Regional Office for the Near East and North Africa conducted a series of webinars under UN Decade for Ecosystem Restoration to prevent, halt and reverse degradation in ecosystems worldwide with the following objectives: to raise awareness on the need for solutions to common problems of degradation and destruction of ecosystems in the Middle East and North Africa region; to strengthen knowledge dissemination by sharing and exchanging best restoration practices; to enhance capacities; and to build a community of practice in the region over the Decade and beyond. This Presentation was performed during the Restoring degraded forests and landscapes in drylands webinar under about the impact of agrosilvopastoral systems restoration to enhance productivity and promote the resilience and sustainably in Tunisia.